A Critical Literature Review on the Interrelatedness between the Frameworks of Cultural Sustainability and Indigenous Identities in Tourism - Jianhong Zhou; Johan R Edelheim (Journal on Tourism & Sustainability, 2021)
The holistic success of Indigenous peoples engaged in tourism stems from focusing on strengthening identities in different contexts, such as political, cultural, economic, or macro, meso, micro, and individual levels. The term ‘cultural sustainability’ highlights cultural integrity, ecological diversity, and socio-economic progress and advocates that the political discourse of local communities should be a positive framework to strengthen Indigenous identities in tourism. The special political and cultural nature of Indigenous identities should, in turn, give impetus to culturally sustainable developments in tourism. Theoretically, using cultural sustainability as a tourism framework to guide Indigenous peoples should bring positive outcomes to tourism enterprises. However, academic tourism research still lacks focus on the interrelatedness between cultural sustainability as a framework and Indigenous identity in tourism. Therefore, this study aims to review this issue critically. Accordingly, an overview of the representations of cultural sustainability as a framework in tourism and the different natures of Indigenous identities are made, and the interrelatedness between cultural sustainability as a framework and Indigenous identities in tourism is discussed. This paper contributes to tourism knowledge by providing critical insights into this interrelatedness and cultivating the positive role of the interrelatedness in tourism practices.